Geometric accuracy of magnetic resonance imaging–derived virtual 3‐dimensional bone surface models of the mandible in comparison to computed tomography and cone beam computed tomography: A porcine cadaver study. (27th July 2021) - Probst, Florian Andreas; Burian, Egon; Malenova, Yoana; Lyutskanova, Plamena; Stumbaum, Maria Juliane; Ritschl, Lucas Maximilian; Kronthaler, Sophia; Karampinos, Dimitrios; Probst, Monika
Abstract: Background: Providing accurate 3‐dimensional virtual bone surface models is a prerequisite for virtual surgical planning and additive manufacturing in craniomaxillofacial surgery. For this purpose, magnetic resonance imaging (MRI) may be a radiation‐free alternative to computed tomography (CT) and cone beam computed tomography (CBCT). Purpose: The aim of this study was to assess the geometric accuracy of 3‐dimensional T1‐weighted MRI‐derived virtual bone surface models of the mandible in comparison to CT and CBCT. Materials and methods: Specimens of the mandible from porcine cadavers were scanned with (1) a 3‐dimensional T1‐weighted MRI sequence (0.6 mm isotropic voxel) optimized for bone imaging, (2) CT, and (3) CBCT. Cortical mandibular structures ( n  = 10) were segmented using semiautomated and manual techniques. Imaging‐based virtual 3‐dimensional models were aligned with a high‐resolution optical 3‐dimensional surface scan of the dissected bone (=ground truth) and global geometric deviations were calculated (mean surface distance [MSD]/root‐mean‐square distance [RMSD]). Agreement between the imaging modalities was assessed by equivalence testing and Bland–Altman analysis. Results: Intra‐ and inter‐rater agreement was on a high level for all modalities. Global geometric deviations (MSD/RMSD) between optical scans and imaging modalities were 0.225 ± 0.020 mm/0.345 ± 0.074 mm for CT, 0.280 ± 0.067 mm/0.371 ± 0.074 mm for MRI, and 0.352 ± 0.076 mm/0.454 ± 0.071 mm for CBCT. All imaging modalities were statistically equivalent within an equivalence margin of ±0.3 mm, and Bland–Altman analysis indicated high agreement as well. Conclusions: The results of this study indicate that the accuracy and reliability of MRI‐derived virtual 3‐dimensional bone surface models is equal to CT and CBCT. MRI may be considered as a reliable alternative to CT and CBCT in computer‐assisted craniomaxillofacial surgery.